MENINJAU KEMBALI PENILAIAN PEMBELAJARAN DALAM PENDIDIKAN SEUMUR HIDUP: HUBUNGAN ANTARA TEKNOLOGI PENDIDIKAN DAN TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGs) : Bahasa Indonesia - Syafaruddin; Ade Aransyah; Undang Rosidin; Rabiyatul Siregar; Handoko (UNDIKMA, 2026)
The transformation of education in the 21st century calls for an assessment system that not only measures academic achievement but also supports the continuous development of competencies aligned with the Sustainable Development Goals (SDGs). This study aims to analyse and reconstruct the concept of learning assessment in sustainable education through the integration of educational technology and artificial intelligence. The study employed a Systematic Literature Review (SLR) method in accordance with the PRISMA 2020 guidelines. Data were obtained from Scopus-indexed international articles published between 2020 and 2025. Following a process of identification, screening and selection based on inclusion and exclusion criteria, 10 articles were identified as eligible for in-depth analysis. Data analysis was conducted using a thematic synthesis approach and interpreted through the Context, Input, Process, Product (CIPP) evaluation model. The findings of the study indicate that lifelong learning requires an assessment system capable of holistically measuring 21st-century competencies, including critical thinking, creativity, collaboration, communication and problem-solving. Educational technology plays a key role in creating flexible, adaptive and data-driven assessments. Artificial intelligence enhances the evaluation process through personalised learning, real-time data analysis, and the provision of more effective feedback. The research findings have produced a conceptual framework for continuous assessment that integrates Education for Sustainable Development (ESD), educational technology, artificial intelligence, and technology-enhanced assessment to support the achievement of the SDGs. This study makes a theoretical contribution to the development of future assessment models that are more inclusive, adaptive, and oriented towards educational sustainability.